Diseño del sistema eléctrico en media y baja tensión para el proyecto de la estación de servicios de combustibles P&S, ubicada en el km 51 de la vía a la Costa. - Zambrano Zambrano, Héctor Iván (2019)
The present titling work details the study and design of a medium and low voltage electrical network for the supply of electric energy to the P & S fuel service station, located at km 51 of the road to the coast. This work is developed in 4 chapters, where the processes step by step for the correct electrical design of the network are presented, based on codes and technical standards, which are the most used by the Electric Companies of Ecuador, when designing electrical systems. In Chapter One we present the approach to the problem, the general objective and the specific ones, as well as the hypothesis, and the methodology we use is descriptive, analytical, explanatory and quantitative. Chapter two deals with everything related to the theoretical framework, information necessary for the reader to be able to interpret basic concepts that will help him to have a clear understanding in the part of the mythology of the work that is presented. Chapter three presents the development of the calculations, standards and technical criteria that are used to make the electrical supply reliable, safe, efficient and continuous, and finally in chapter four it is concluded that the development of this project allowed expanding the knowledge in medium and low voltage installations. As far as the recommendations are concerned, it is indicated that the technical standards established in the NATSIM must be followed.